2019
DOI: 10.1177/1049909119892591
|View full text |Cite
|
Sign up to set email alerts
|

A Public Health Approach to Palliative Care in the Canadian Context

Abstract: Palliative care helps improve the quality of life of individuals facing life-limiting illness throughout the course of their disease. In Canada, delivery and access to palliative care has been fraught with challenges including differential availability of services based on geography, funding, language, and socioeconomic status. Many groups, including the World Health Organization, have advocated for a public health approach to palliative care as an antidote to fragmented service delivery. Multiple scholars, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Although our review did not highlight the infrastructure context, policies are needed at multiple levels in order to create health and social structures that will normalize and facilitate an upstream approach for palliative care. For example, the public health approach to palliative care advocates for policy development and implementation in the practice, health system, and societal contexts [ 86 ]. Societal contexts that embrace the public health approach to palliative care and align with the Compassionate Communities model [ 35 ] can catalyze social changes in attitudes that reinforce health system policies.…”
Section: Discussionmentioning
confidence: 99%
“…Although our review did not highlight the infrastructure context, policies are needed at multiple levels in order to create health and social structures that will normalize and facilitate an upstream approach for palliative care. For example, the public health approach to palliative care advocates for policy development and implementation in the practice, health system, and societal contexts [ 86 ]. Societal contexts that embrace the public health approach to palliative care and align with the Compassionate Communities model [ 35 ] can catalyze social changes in attitudes that reinforce health system policies.…”
Section: Discussionmentioning
confidence: 99%
“…Our first interest was to map and categorise the geographical locations of the reported work. Expressions related to varied jurisdictions; some global [32], some regional, like 'Central and Eastern Europe' [33] and 'Latin America' [34], whilst others focussed on individual nation states such as, Canada [35], South Africa [36] and Norway [37]. In wider terms, this distribution can be seen in relation to the six regions of the WHO (with an additional 'global' category).…”
Section: Geographical Contextmentioning
confidence: 99%
“…For example: the prominence of policy [21]; degrees of integration [112]; funding allocated to PC [33]; the extent of specialist services [20]; levels of access to medicines [9]; workforce 'capacity' [87]; and the extent of training and education [53]. These were expressed as either stand-alone variables or more systematically [35] as a suite of actions [113] and composites presented in various forms -'atlases' [114], 'mapping' exercises [115] or 'league tables' [116]. Beyond these pragmatic orientations, two contrasting 'policy logics' were visible in the form of ethically-based practice values [117].…”
Section: Grounded Problematisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Equity impact assessment of palliative care policies has been conducted in some countries such as the UK to identify equity needs and gaps, monitor inclusion progress, and to ensure that policies and initiatives do not inadvertently create inequity [ 18 , 20 ]. An analysis of palliative care policies in Canada found that although inequity is well-documented, the policy and political contexts hinder the incorporation of public health approaches in palliative care [ 21 ].…”
Section: Introductionmentioning
confidence: 99%